Selected Locations for Potato Industry Cultivation in Indonesia using the Weighted Product Method - Rio Reyno Elia; Nastiti Siswi Indrasti; Ono Suparno (Institut Pertanian Bogor, 2026)
PT. ABCD, the world's largest potato chip maker, relies on industrial-grade potatoes grown in conjunction with Indonesian farmers. This study addressed the topic of selecting the best subdistrict locations for industrial potato growing by combining agroclimatic and non-agroclimatic variables. The goal was to determine the best cultivation areas based on agroclimatic variables (temperature, rainfall, sunlight duration, cloud cover, radiation, altitude, frost risk) and non-agroclimatic variables (harvested area, production, productivity, logistics, pest and disease incidence, irrigation, production costs, competition, and farmer capability). The Weighted Product (WP) technique was used in the study to assign weights to each criterion and evaluate alternatives through a ranking procedure. Data were gathered from PT ABCD's agroclimatic database (2010−2020) and processed using ArcGIS, supplemented by secondary data from the Central Bureau of Statistics and field surveys. The results identify the ten most suitable subdistricts for industrial potato cultivation as Batur (Banjarnegara, Central Java), Tosari (Pasuruan, East Java), Pasir Wangi (Garut, West Java), Cikajang (Garut, West Java), Sirampog (Brebes, Central Java), Pejawaran (Banjarnegara, Central Java), Bawang (Batang, Central Java), Kayu Aro (Kerinci, Jambi), Pangalengan (Bandung, West Java), and Kejajar. The study shows that the WP technique efficiently incorporates agroclimatic and non-agroclimatic factors in site selection. These findings provide a solid foundation for strategic decision-making in the potato chip sector, helping to identify appropriate cultivation areas to assure long-term supply and competitiveness.Keywords: chip grade, potato cultivation, land evaluation, agroclimatic variables, weighted product method